Peranan Badan Permusyawaratan Desa (BPD) terhadap Pelaksanaan Otonomi Desa di Desa Allakuang - Musawwama Musawwama (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract This research aimed to determine the role of Village Consultative Corporation (what we call BPD) on the implementation of village autonomy in Allakuang Village along with all influencing factors. This research was a descriptive type using a case study approach, held in Allakuang Village at Maritengngae District of Sidenreng Rappang Regency. The population was 704 heads of family and 70 samples. Datas were collected through observation, interviews, questionnaire with BPD members and community of Allakuang Village. The results showed that the role of Village Consultative Corporation on the implementation of village autonomy in Allakuang Village was not run optimally. From the legislative function, the role was rated good at 75,71%, a very good representation of 80%, and a good 61,42% rate in functions control. The influencing factors were the poor education at 47,14%, unfavorable experience at 50%, and an adequate infrastructure at 61,42%.